Correlates of delayed disease progression in HIV-1-infected Kenyan children. - Chakraborty, R; Morel, A; Sutton, J; Appay, V; Ripley, R; Dong, T; Rostron, T; Ogola, S; Palakudy, T; Musoke, R; D'Agostino, A; Ritter, M; et al. (2005)
Without treatment most HIV-1-infected children in Africa die before their third birthday (>89%) and long-term nonprogressors are rare. The mechanisms underlying nonprogression in HIV-1-infected children are not well understood. In the present study, we examined potential correlates of delayed HIV disease progression in 51 HIV-1-infected African children. Children were assigned to progression subgroups based on clinical characterization. HIV-1-specific immune responses were studied using a combination of ELISPOT assays, tetramer staining, and FACS analysis to characterize the magnitude, specificity, and functional phenotype of HIV-1-specific CD8(+) and CD4(+) T cells. Host genetic factors were examined by genotyping with sequence-specific primers. HIV-1 nef gene sequences from infecting isolates from the children were examined for potential attenuating deletions. Thymic output was measured by T cell rearrangement excision circle assays. HIV-1-specific CD8(+) T cell responses were detected in all progression groups. The most striking attribute of long-term survivor nonprogressors was the detection of HIV-1-specific CD4(+) Th responses in this group at a magnitude substantially greater than previously observed in adult long-term nonprogressors. Although long-term survivor nonprogressors had a significantly higher percentage of CD45RA(+)CD4(+) T cells, nonprogression was not associated with higher thymic output. No protective genotypes for known coreceptor polymorphisms or large sequence deletions in the nef gene associated with delayed disease progression were identified. In the absence of host genotypes and attenuating mutations in HIV-1 nef, long-term surviving children generated strong CD4(+) T cell responses to HIV-1. As HIV-1-specific helper cells support anti-HIV-1 effector responses in active disease, their presence may be important in delaying disease progression.